2017
DOI: 10.1103/physrevb.96.235106
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the orbital and spin ordering in rare-earth titanates

Abstract: Rare-earth titanates RTiO3 are Mott insulators displaying a rich physical behavior, featuring most notably orbital and spin orders in their ground state. The origin of their ferromagnetic to antiferromagnetic transition as a function of the size of the rare-earth however remains debated. Here we show on the basis of symmetry analysis and first-principles calculations that although rare-earth titanates are nominally Jahn-Teller active, the Jahn-Teller distortion is negligible and irrelevant for the description … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 40 publications
4
35
0
Order By: Relevance
“…We have previously identified 33 We conclude that the electronically-induced Jahn-Teller distortion mode Q2and the geometrically induced steric Q2 + octahedral deformation mode are fully captured by a static mean-field method. This is in line with recent theoretical works that have demonstrated that static mean-field methods capable of inducing broken symmetry such as Density Functional Theory 13,26,30,33 in a polymorphous representation suffice to also explain (i) the trends in gapping and type of magnetic order across the ternary ABO3 series 33…”
Section: A Landau-esque Perturbation Approachsupporting
confidence: 88%
“…We have previously identified 33 We conclude that the electronically-induced Jahn-Teller distortion mode Q2and the geometrically induced steric Q2 + octahedral deformation mode are fully captured by a static mean-field method. This is in line with recent theoretical works that have demonstrated that static mean-field methods capable of inducing broken symmetry such as Density Functional Theory 13,26,30,33 in a polymorphous representation suffice to also explain (i) the trends in gapping and type of magnetic order across the ternary ABO3 series 33…”
Section: A Landau-esque Perturbation Approachsupporting
confidence: 88%
“…Among transition‐metal perovskites, rare‐earth orthorhombic titanates RTiO 3 (R = La… Lu or Y) emerge as a particularly interesting family of Mott insulators . The most stable valence state of rare‐earths (except for Eu and Ce) is 3+, which imposes a 3+ valence state to the Ti that is in a spin ½ 3d 1 electronic state.…”
mentioning
confidence: 99%
“…In the undistorted cubic perovskite SrVO 3 , the three t 2g bands are degenerated with an effective band‐filling of 1/6 favoring the correlated metal phase. In the distorted titanates, however, the splitting of the t 2g levels gives rise to Mott insulating behavior . Stoichiometric LaTiO 3 is therefore a prototypical single band Mott insulator and, as indicated by its small Mott gap, already close to the transition into the correlated metal phase.…”
mentioning
confidence: 97%